STRATEGI PENINGKATAN KUALITAS LAYANAN DAN KEPRIBADIANSEBAGAI VARIABEL INTERVENING PENGARUH KUALITAS LAYANAN PADA INTENSI BERPERILAKU PASCA PEMBELIAN - Siti Almaidah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to test and analyzethe influence of service quality on intentionsbehavepost purchasewith a service quality improvement strategyand personalityas intervening variable.The sample used in this study amounted to 100customers of Branch Office of BCA Solo Veteran. Sampling technique usingaccidental sampling technique,customers who are sampled are customers whomake transactions during research.Methods of data analysis using validity test,reliability test, classical assumption test, and path analysis.Based on the resultsof data analysis obtained:(1) service quality significantly influencespostpurchase behavior intention, the direct effect is 0,303 and t value 2,680.(2)service quality significantly influence service quality improvement strategy,with direct influenceis 0,625 and t value is 7,924.(3) service qualitysignificantly influence on personality, the direct effect is 0.582and t value is7,084,(4) service quality significantly influences post-purchase behaviorintentions through service quality improvement strategies,with direct influenceof 0.303 and indirect influence of 0.157,and (5) service quality significantlyinfluence intention to behave after purchasing through personality with directinfluence equal to 0,303 and indirect influence 0,152. Keywords:  Quality of service, The intentions of post-purchase behavior,Strategy to improve service quality, Personality.